Measuring fifty years of trade globalization - Palan, N.; Simões, N.; Crespo, N. (The World Economy, 2021)
Although trade globalization is a multi-faceted phenomenon, researchers often capture its magnitude by trade volume alone. In order to gain a deeper understanding of the phenomenon we propose measures that also account for the interconnectedness of countries, for geographical distance, and for the role of individual sectors in bilateral trade. We also improve upon existing indices by moving from a country-level analysis (internationalization) to a truly global perspective (globalization). We measure trade globalization using data from CHELEM (CEPII) over a period of 50 years, covering 72 countries for the sub-period 1967–1990 and 84 countries for 1994-2016. The results show substantial increases in all dimensions of globalization, despite substantial differences between the measures, highlighting the need to analyze globalization with a comprehensive set of indicators. Regarding the number of positive bilateral trade flows, globalization was almost completed by 2016. The importance of distance also diminished throughout the period analyzed, but neighboring countries still share stronger trade relations. Results indicate that trade globalization for high-tech sectors varies significantly from the evolution seen in other sectors, especially large, low-tech sectors. The latter tend to show the highest level of trade globalization over the whole period, but the former group could catch up considerably.